Migration Policymaking in Europe The Dynamics of Actors and Contexts in Past and Present - Penninx, Rinus; Borkert, Maren; Zincone, Giovanna (Amsterdam University Press, 2011)
This important work analyses immigration and immigrant inclusion policies in ten European countries, examining how such policies are formed and subsequently implemented. The study singles out the important role of usually overlooked factors and actors that significantly affect policymaking alongside the formal legal framework. It also identifies similarities and diversities in European immigration policies.